2020
DOI: 10.13106/jafeb.2020.vol7.no11.769
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Firm Value and Profitability: Evidence from Indonesia

Abstract: The purpose of this study was to examine the role of profitability as a mediating variable in influencing firm value. This study uses a sample of manufacturing companies listed on the Indonesia Stock Exchange from 2016 to 2018. The data used is panel data, with data analysis using multiple regression. Based on the Sobel test, profitability plays a role in mediating the effect of firm size on firm value. The effect of firm size on firm value is indirect, however, through profitability. Therefore, the market pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
36
1
25

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 14 publications
11
36
1
25
Order By: Relevance
“…This result is in accordance with the view expressed which states that the larger the debt-based capital structure as a burden on the company, the lower the financial performance. And the declining level of profitability is caused by the costs that must be borne by the company when they use a high level of debt [16], [17], [18].…”
Section: Methods and Research Datamentioning
confidence: 99%
See 1 more Smart Citation
“…This result is in accordance with the view expressed which states that the larger the debt-based capital structure as a burden on the company, the lower the financial performance. And the declining level of profitability is caused by the costs that must be borne by the company when they use a high level of debt [16], [17], [18].…”
Section: Methods and Research Datamentioning
confidence: 99%
“…The right theory to relate the influence of financial performance to firm value is signaling theory about how companies should signal to users of reports in the form of information about the company's financial performance [19]. There is a less expensive method for companies to signal to investors that the company can ISSN: 2722-4015 http://ijstm.inarah.co.id issue announcements about the company's prospects and ability to generate profits by hiring outsiders to examine the company's books or other materials and provide an opinion on whether managers are telling the truth [20], [21].…”
Section: Methods and Research Datamentioning
confidence: 99%
“…The Debt to Equity Ratio measures capital structure (DER). Several earlier studies concluded that capital structure reduces corporate value [1]. Others concluded that capital structure positively impacts corporate value [2].…”
Section: Introductionmentioning
confidence: 99%
“…Profitability measures a company's capacity to make money from sales and investments. Profitability has been shown to positively impact business value [1,17,18]. Various studies claim that profitability has no impact on firm value [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation